The CON-SOT-LOT Test for Nonorganic Hearing Loss - Martin, Jeffrey S.; Martin, Frederick N.; Champlin, Craig A. (Journal of the American Academy of Audiology, 2000)
The efficacy of a screening procedure for detecting nonorganic hearing loss using standard audiometric instrumentation was examined. Thirty normal-hearing subjects' responses to continuous and standard and lengthened off-time pulsed tones, using an ascending-descending method, were compared. Subjects were asked to respond to test stimuli in normal-hearing and simulated hearing loss conditions. Data show that there are clinical and statistical differences between subjects' response patterns in the normal-hearing condition as compared to the feigned hearing loss condition. The procedure is offered as a simple method of screening for nonorganic hearing loss.Abbreviations: A-D = ascending-descending, ANOVA = analysis of variance, CON = continuous tone, LOT = lengthened off-time pulsed tone, MML = modified method of limits, NOHL = nonorganic hearing loss, STL = simulated threshold level, SOT = standard off-time pulsed tone
Keywords: Ascending-descending method; nonorganic hearing loss; screening procedure